2017
DOI: 10.5817/sp2017-3-7
|View full text |Cite
|
Sign up to set email alerts
|

Osvojování dovednosti čtení očima matek žáků 1. tříd

Abstract: Abstrakt

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…Sénéchal & LeFevre, 2014, who report that 76% of the parents surveyed performed activities or adjusted activities in relation to the child's school results). Drawing on this research, in a previous paper (Sedláčková, 2017), I identified three qualitatively different reading aspirations among the mothers in my data that could not easily be ranked from "lowest" to "highest", since each concerned the development of different reading literacy areas: a) mothers with practical reading aspirations wanted their children to master reading well enough for use in everyday life; (b) mothers with experiential reading aspirations wanted their children to enjoy reading and to develop a positive relationship with books and reading; c) mothers with developmental reading aspirations thought it important for their children to acquire reading skills as a value for further development. There can be some overlaps in these different types of aspirations, but only partial.…”
Section: Various Concepts Of Parental Reading Aspirations For Their Cmentioning
confidence: 92%
See 4 more Smart Citations
“…Sénéchal & LeFevre, 2014, who report that 76% of the parents surveyed performed activities or adjusted activities in relation to the child's school results). Drawing on this research, in a previous paper (Sedláčková, 2017), I identified three qualitatively different reading aspirations among the mothers in my data that could not easily be ranked from "lowest" to "highest", since each concerned the development of different reading literacy areas: a) mothers with practical reading aspirations wanted their children to master reading well enough for use in everyday life; (b) mothers with experiential reading aspirations wanted their children to enjoy reading and to develop a positive relationship with books and reading; c) mothers with developmental reading aspirations thought it important for their children to acquire reading skills as a value for further development. There can be some overlaps in these different types of aspirations, but only partial.…”
Section: Various Concepts Of Parental Reading Aspirations For Their Cmentioning
confidence: 92%
“…In the Czech Republic, much attention is being devoted to reading comprehension difficulties (as a result of comparatively lower student scores on the PISA and PIRLS tests) (Wildová, 2012b;Wildová, Kropáčková, & Kucharská, 2014). In addition to these problems, the mothers in my research (Sedláčková, 2017) also mentioned a lack of interest in reading, which on one hand could extend beyond the scope of the list provided above, but on the other could be seen as possibly permeating it. Case et al (2010) argue that parents are able to assess their child's reading skills relatively accurately.…”
Section: Parental Perceptions Of Children's Reading Difficultiesmentioning
confidence: 98%
See 3 more Smart Citations